التقابل اللغوى وتحليل الأخطاء في اللغة العربية - Khoirun Nisa'; Fahrur Rosikh (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2021)
Error analysis is an analytical study of linguistic errors committed by an individual or group of individuals during the production of the first second language in speech or book. This analysis is concerned with classifying errors from two aspects: linguistic classification, such as grammatical errors, spelling, writing, or semantics. The Sinaitic classification is a mistake due to the first language to the second language, or a coincidental error. Error analysis focuses on the target language, it is known that there is a difference between languages in several areas and from structures, book and sound. This difference causes problems for students in learning the target language and makes mistakes in some areas, and the analysis reveals all the errors found. Grammatical errors include phonemes, morphology, and grammar, and the results of the book research indicated that grammatical errors are more frequent when a foreign language learner in the process of linguistic skill, and because one of the goals of teaching grammar rules in education stages is to establish the tongue and reduce melody in speech, the learner reads, speaks, or books He did not raise up, nor did he shorten erect.